Identification Of Fast Growing Areas In South Halmahera (Case Study In 9 Sub-Districts) - Farahdilla S Djama*; Said Mala; Fahima Nasar; Musdar Muhammad (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research aims to; Determine sub-districts that have the potential to become growth centers, and Know the interactions between sub-districts. The method used is scalogram analysis to determine growth centers and the gravity method to determine the potential interaction between sub-districts. The results showed that Bacan Sub-district, East Gane Sub-district, West Gane Sub-district, Kayoa Sub-district, and Obi Sub-district, can be used as regional growth centers, while West Bacan Sub-district, East Bacan Sub-district, Makian Sub-district, and South Obi Sub-district, as hinterland. The highest potential interaction occurs between Bacan sub-district and East Bacan sub-district with a potential value of 5.50 while the lowest occurs in Makian sub-district with East Gane sub-district with a potential value of 0.01.